Alcohol scale: validity and reliability study in cigarette addict students - Çetin, Ebru; Cantürk, Nergis; Dağalp, Rukiye (Journal of Dependence, 2019)
Objective: The aim of this study is to make the validity and reliability studies of Alcohol Scale developed by Ögel et. al in Ankara University cigarette addict students.Method: The sample of this study consisted of 120 voluntary students from Ankara University who were cigarette addict students of faculty of law, faculty of medicine and engineering faculty. There are a total of 6 items in the Alcohol Scale. The study data were collected with the Informed Voluntary Form and the Alcohol Scale consisting of 6 items.Results: As a result of the validity analysis of the scale, the Kaiser-Meyer-Olkin (KMO) value was 78.5%, the Barlett’s Test of Sphericity chi-square value was found to be 236.847. The Cronbach alpha coefficient of the scale was 0.805 and it was found to have a strong degree of reliability.Conclusion: The Alcohol Scale has a good level of reliability and sufficient validity. The scale is recommended to be used for evaluating the alcohol dependence of cigarette addict university students.
Keywords: Alcohol scale; validity; reliability; university student